Anticancer activity of Curcuma aeroginosa essential oil and its nano-formulations: cytotoxicity, apoptosis and cell migration effects - Pawaret Panyajai; Natsima Viriyaadhammaa; Singkome Tima; Sawitree Chiampanichayakul; Pornngarm Dejkriengkraikul; Siriporn Okonogi; Songyot Anuchapreeda (BMC, 2024)
Abstract Background and aims Curcuma aeruginosa, commonly known as "kha-min-dam" in Thai, holds significance in Asian traditional medicine due to its potential in treating various diseases, having properties such as anti-HIV, hepatoprotective, antimicrobial and anti-androgenic activities. This study explores the anticancer activity of C. aeruginosa essential oil (CAEO) and its nano-formulations. Methods CAEO obtained from hydrodistillation of C. aeruginosa fresh rhizomes was examined by gas chromatography mass spectroscopy. Cytotoxicity of CAEO was determined in leukaemic K562 and breast cancer MCF-7 cell lines using an MTT assay. Cell cycle analysis and cell apoptosis were determined by flow cytometry. Cell migration was studied through a wound-healing assay. Results Benzofuran (33.20%) emerged as the major compound of CAEO, followed by Germacrene B (19.12%) and Germacrone (13.60%). Two types of CAEO loaded nano-formulations, nanoemulsion (NE) and microemulsion (ME) were developed. The average droplet sizes of NE and ME were 13.8 ± 0.2 and 21.2 ± 0.2 nm, respectively. In a comparison with other essential oils from the fresh rhizomes of potential plants from the same family (Curcuma longa, Curcuma mangga and Zingiber officinale) on anticancer activity against K562 and MCF-7 cell lines, CAEO exhibited the highest cytotoxicity with IC50 of 13.43 ± 1.09 and 20.18 ± 1.20 µg/mL, respectively. Flow cytometry analysis revealed that CAEO significantly increased cell death, evidenced from the sub-G1 populations in the cell cycle assay and triggered apoptosis. Additionally, CAEO effectively inhibited cell migration in MCF-7 cells after incubation for 12 and 24 h. The developed NE and ME formulations significantly enhanced the cytotoxicity of CAEO against K562 cells with an IC50 of 45.30 ± 1.49 and 41.98 ± 0.96 µg/mL, respectively. Conclusion This study's finding suggest that both nano-formulations, NE and ME, effectively facilitated the delivery of CAEO into cancer cells.